Risk factors associated with treatment abandonment by overweight or obese children and adolescents - Soares Mariz, Larissa; Campos Muniz Medeiros, Carla; Cruz Enders, Bertha; Nascimento Kluczynik Viera, Caroline Evelin; Aires Silva Medeiros, Kaio Keomma; Silva Coura, Alexsandro (Investigación y Educación en Enfermería, 2016)
Objective. To evaluate the risk factors associated with treatment abandonment by overweight or obese children and adolescents. Methods. A cross-sectional study, conducted in 2011, at the Childhood Obesity Center, in Campina Grande, Brazil, with the records of 208 children and adolescents, between three and 18 years of age, divided into two groups: Group I included those who abandoned treatment, and Group II included those who did not abandon treatment. Results. Non-adherence was significantly associated with higher income (OR=5.8), high maternal education (OR=2.4), white skin color (OR=2.9), and obesity (OR=3.6). Conclusion. Despite the new academic-care approach, the non-adherence to treatment rate was high, and was associated with sociodemographic and nutritional factors. How to cite this article: Mariz LS, Medeiros CCM, Enders BC, Vieira CENK, Medeiros KKAS, Coura AS. Risk factors associated with treatment abandonment by overweight or obese children and adolescents. Invest. Educ. Enferm. 2016; 34(2):